PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA ZOYA BANJARMASIN - Apriliani, Ayu; Wahyuni, Nurul (Universitas lambung Mangkurat, 2020)
Ayu Apriliani, D1A212034, 20 1 9, The Effect of Product Quality and Price on Decision Purchase on Zoya Banjarmasin. Skripsi, Business Administration Study Program. Advisor: Nurul WahyuniThis study aims to determine and test significant influence in partial Quality Products to Purchase Decision on Zoya, for determine and test the effect of significant influence in partial Price of the Purchase Decision on Zoya and to identify and test significant influence variables simultaneously Product Quality and Price Decision to Purchase on Zoya.The research method used is a quantitative approach to the type of research explanatory research. Samples taken as many as 85 usingnon-probability sampling, collecting data using questionnaires, while data analysis using Multiple Regression Analysis with SPSS version 23.The results of the testing to prove it partially Products (X1) of the Decision Purchase (Y) by 92%, price (X2) of the Decision Purchase (Y) amounted to 58.2% and is simultaneously Quality Products (X1) and Price (X2) to decision Purchase (Y) amounted to 87.6% while the rest of 12.4 % is influenced by variables other were not investigated